Comparison of the Brain and Medulla Spinalis Ultrastructural Evaluation Using Five Different Fixatives - Ferda Topal Çelikkan; Esra Erdemli (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:Ultrastructural examination of nervous tissues is essential for neuroscientific study. Nervous tissue is sensitive to ischemia and hypoxia. Thus, the fixation and process of this tissue is critical for evaluating ultrastructure of nervous tissue. It is difficult to distinguish whether the findings are due to the fixative used in the experimental research or the experimental agent. In this study, we aimed to investigate the effects of the different five fixatives on the brain and medulla spinalis, which are the central nervous system organs, by evaluating the ultrastructural changes.Materials and Methods:In this study, five male Wistar Albino rats (200-250 gr) were anesthetized. The perfusion fixation was performed by 4% paraformaldehyde (PFA). The extracted brain and medulla spinalis pieces were immersed into five different fixation solutions as (I) Trump’s solution 4% PFA and 1% glutaraldehyde (GA), (II) 2% PFA and 2.5% GA with 2.5 mM CaCl, (III) 2% PFA and 2.5% GA, (IV) 2.5% GA, (V) Trump’s solution 4% PFA and 1% GA (1% OsO4 containing potassium ferrocyanate). After routine processes, all ultrathin tissue sections were investigated under the transmission electron microscopy.Results:In Group 4, the cell nucleus, perinuclear space, mitochondrion, rough endoplasmic reticulum and myelin sheet, endothelium and basal lamina of nervous tissues of brain and medulla spinalis were evaluated as normal ultrastructure compared to the other groups.Conclusion:In present study, we showed that 2.5% GA solution prepared with cacodylate buffer was convenient and effective for nerve tissues of electron microscopic routine process.